2009
DOI: 10.1177/1538574409335274
|View full text |Cite
|
Sign up to set email alerts
|

Carotid Body Tumor Surgery: Management and Outcomes in the Nation

Abstract: CBT resection is a relatively rare procedure and when combined with EMB was more expensive, but was associated with significantly fewer complications and decreased blood product utilization. These data suggest that CBT surgery requiring carotid reconstruction carries significant morbidity and that EMB as an adjunctive tool was beneficial for CBT surgery outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 24 publications
1
37
1
Order By: Relevance
“…Embolization reduces morbidity and mortality and shortens the time of surgery by reducing intraoperative bleeding. This was demonstrated by Vogel et al, 15 who evaluated 2117 patients with carotid body tumors and found significantly fewer complications and decreased blood product requirements when resection was combined with preoperative embolization. Small paragangliomas are usually easier to resect; however, no study to date has evaluated the benefits and risks of embolization according to tumor size.…”
Section: Discussionmentioning
confidence: 79%
“…Embolization reduces morbidity and mortality and shortens the time of surgery by reducing intraoperative bleeding. This was demonstrated by Vogel et al, 15 who evaluated 2117 patients with carotid body tumors and found significantly fewer complications and decreased blood product requirements when resection was combined with preoperative embolization. Small paragangliomas are usually easier to resect; however, no study to date has evaluated the benefits and risks of embolization according to tumor size.…”
Section: Discussionmentioning
confidence: 79%
“…We do not usually perform preoperative embolization (only 2 patients before 1992, for > 4 cm tumor, for which embolization was only partial), although it has recently been reported not to be associated with increased risk of stroke [17]. Most authors report little benefit in postoperative course, with no evidence of a decrease in morbidity in general or in cranial nerve deficit in particular [15].…”
Section: Discussionmentioning
confidence: 96%
“…The contribution of preoperative embolization is controversial [5,9,[15][16][17]. We do not usually perform preoperative embolization (only 2 patients before 1992, for > 4 cm tumor, for which embolization was only partial), although it has recently been reported not to be associated with increased risk of stroke [17].…”
Section: Discussionmentioning
confidence: 99%
“…According to Makeieff et al [17], the rate of serious complications (i.e., permanent nerve palsy, vascular complications) was 2.3 % for Shamblin Class I/II tumors and 35.7 % for Shamblin Class III tumors. Nevertheless, internal carotid resection with or without vascular reconstruction when the artery is enveloped by the tumor has been reported in as much as 12.5-18 % of surgically treated patients [5,18,19]. According to Vogel et al [19] who carried out a systematic review including 1988 patients who underwent CBT surgery, those with reconstruction of the carotid artery had significantly greater rate of mortality (1.61 vs. 0.59 %) and stroke (17.7 vs. 3.5 %) compared to the rest of patients.…”
Section: Treatment Of Carotid Body Paragangliomasmentioning
confidence: 99%
“…Nevertheless, internal carotid resection with or without vascular reconstruction when the artery is enveloped by the tumor has been reported in as much as 12.5-18 % of surgically treated patients [5,18,19]. According to Vogel et al [19] who carried out a systematic review including 1988 patients who underwent CBT surgery, those with reconstruction of the carotid artery had significantly greater rate of mortality (1.61 vs. 0.59 %) and stroke (17.7 vs. 3.5 %) compared to the rest of patients. To summarize, although ''wait and scan'' is an option in most of the patients younger than 60 years with a single Class I CBT, surgery should be considered as the first choice therapy, since under these circumstances it produces minimal morbidity, almost no mortality, and a very good chance to really cure the patient.…”
Section: Treatment Of Carotid Body Paragangliomasmentioning
confidence: 99%